Argentine heritage buildings: Old school home: Energetic assessment. Rehabilitation criteria for an improved performance (ARQUISUR Revista, 2014)
Argentina houses a number of buildings spread all over the country and built in capital cities like Buenos Aires, Mendoza, Salta, Corrientes and Resistencia. They constitute part of the Argentine historical, cultural, and national heritage once flourished in times of President Juan Domingo Peron’s administration in the 1950s. Some of them were converted into important Institutions which function as venues for National organisms or departments. This is the case of the Universidad Nacional del Nordeste (UNNE) located in the site of an Old school Home built in Resistencia, capital of Chaco, in the 1950’s, which holds colleges on various fields such as Architecture, Engineering, or others alike. The present report outlines results of the research carried out in order to measure the barely adequate performance of the lighting and hydrothermal conditions that the current building of the Architecture College presents. A final diagnosis has allowed putting forward measures to implement thoro.
Keywords: building envelopes; hydrothermal / energetic diagnosis; improvement; rational energy use